Penyusunan Strategi Pemasaran Digital dan Modul Pelatihan Karyawan Pada Toko Central Legenda Laundry - Hesniati Hesniati; Erlen Erlen (Universitas Internasional Batam, 2021)
This digital marketing strategy is drafted for Toko Central Legenda Laundry aims to help the owner to improve sales, introducing their service in an digital platform, improving market reach, and to promote the services and quality of the business. In the past, Toko Central Legenda laundry was uses a traditional form of marketing strategy. The digital marketing strategy is drafted based on information collected by the author through interviews and observation. The strategy revolves around social media (Instagram and Facebook) and training module for employees. Based on the draft of this digital marketing strategy, the social media account has an steady increase in numbers of follower, steady increased profitability and results are positive.